Language Teachers at Work Linking Materials with Classroom Teaching - Li, Zhan.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2020)
This book examines a ubiquitous, yet under-researched, area of language education, i.e., language teachers' use of curriculum materials. It particularly focuses on EFL teachers' use of prescribed curriculum materials in higher education in Mainland China and presents a qualitative, multi-case study involving four Chinese EFL teachers and eight students (two students from each teacher$1 (Bs class) at one university in Mainland China. Drawing on data from pre-lesson and post-lesson interviews with the teachers, lesson observations, and documents in three consecutive semesters at the target university, the book delineates the processes of materials use in classroom settings. It also identifies four domains of factors that influenced the enactment of curriculum materials. Most importantly, by adopting Vygotsky$1 (Bs (1978) mediation theory and Remillard$1 (Bs (2005) participatory perspective, the book constructs a "curriculum enactment mediation model" to reveal the complex and mediated relations among teachers, learners, curriculum materials, and context. It also recommends practical implications for materials developers, teacher educators, administrators, and policymakers.s
Chapter 1 Introduction -- Chapter 2 Teachers$1 (Buse of materials: A sociocultural perspective -- Chapter 3 The design of the study -- Chapter 4 Teachers$1 (Buse of curriculum materials -- Chapter 5 Discussion -- Chapter 6 Conclusions and implications.s
Keywords: Curriculums (Courses of study).; Education$1 (BCurricula.s; Language and education; Sociolinguistics; Curriculum Studies; Language Education; Sociolinguistics